Multidirectional Lineament Analysis from DEMNAS Digital Elevation Model, Application for Detection Permeability Zone Tulehu Geothermal Field, Central Moluccas - Erwin Bakker (Jurnal Geosains dan Remote Sensing, 2024)
The morphological lineament on the surface detected by satellite imagery expresses the geological structure in the form of faults, fractures, joints, and other geological structures. Identification of geological lineaments is useful for analyzing tectonic history, exploring geological resources, and mitigating geological disasters. Exploration of geological resources, one of which is geothermal, continues to be developed to meet the world's growing energy needs. Therefore, the main objective of this study is to extract lineaments using the multidirectional irradiation method from DEMNAS images applied to analyze the permeable zone in the Tulehu geothermal field, Central Moluccas. To optimally identify the geological lineament, lineament extraction is carried out using the multidirectional irradiation method from DEMNAS imagery which has a spatial resolution of 0.27 arcs, which is then quantified lineament density in a grid with an area of 1x1 km2. The quantification result of the highest lineament density is 3.47 km/km2. The permeability zone at the study site is at a lineament density value greater than 1.6 km/km2, which is associated with sedimentary rocks and lithological boundaries. Overall, the multidirectional method of DEMNAS images produces detailed visual images so that lineament extraction can be carried out optimally.